Mandarin Chinese in 30 days course work - Swihart, De-an Wu (Berlitz, 2008)
Helps you learn everyday Chinese Mandarin. This title provides 30 lessons focusing on daily routines, business, travel and more. It includes 2 audio CDs that feature recordings of all the dialogues in the course book and 6 tests allow the user to test themselves to measure their proficiency.